A Habitual Action of Listening to Songs in a Writing Class - Wijirahayu, Suciana; Sutiwan, Adji Saputra (Universitas Siliwangi, 2023)
The behaviour of learners in listening to English songs will create a habit, or activity carried out periodically or repeatedly. Learners who always listen to English songs form habitual actions that may affect their language learning process, especially vocabulary acquaintance. The habit of listening to English songs offers occasions to learn the language. The learners who have the habit of listening to English songs will have more vocabulary since they are used to listening to many words in the lyrics. Mastery of vocabulary in writing is essential. Writing is one of the complex language skills because it involves the ability of writing techniques and language skills. With poor vocabulary mastery, students find it difficult to string words together to make a sentence because they lack the vocabulary to represent their writing. Students with good vocabulary mastery were able and easy to string words. They can determine diction for their writing. Keywords: vocabulary mastery; habit of listening to the song.